Environmental Stability of Carbohydrate Profiles in Different Soybean Genotypes. Issue 2 (1st March 2018) - Jo, Hyun; Lee, Jeong‐Dong; Bilyeu, Kristin D.
Abstract : Soybean [ Glycine max (L.) Merr.] is an important annual crop. The raffinose family oligosaccharides (RFOs) raffinose and stachyose are antinutritional carbohydrates present in soybean seeds. Consumption of soybean seed products with low RFO reduced flatulence in humans and increased metabolizable energy efficiency in chickens, pigs, and dogs. The development of soybean cultivars producing high metabolizable energy with low antinutritional factors in the seed is one avenue to increase soybean value. The soybean line PI 200508 with low RFO content was previously characterized to have a reduction of seed raffinose synthase enzyme activity. A variant allele of the raffinose synthase 2 gene ( RS2 ) with a 3‐bp deletion leading to the elimination of a single conserved amino acid residue ( RS2, rs2W331 −) in PI 200508 was associated with the seed RFO phenotype. Another missense allele of RS2 and variant alleles of the RS3 gene have been identified. The objective of this study was to determine the environmental stability of the carbohydrate profiles for soybean lines containing different allele combinations of two key raffinose synthase ( RS2 and RS3 ) genes in two locations over 2 yr. Although this study was conducted with different genetic backgrounds, the results indicated that the carbohydrate profile in soybean seed is mostly determined by RS2 and RS3 genotype, and galactinol and sucrose content were mainly affected by environmental factors. Genotype was the major factor for the RFO content in soybean seeds, and soybean lines with the rs2W331 − allele of RS2 were the most stable for sucrose and RFOs over four environments. A novel genetic combination of RS2 and RS3 alleles demonstrated the importance of multiple variant alleles contributing to seed raffinose synthase activity.